Analisis Tingkat Efektivitas Program Subsidi Pupuk dari Pemerintah terhadap Pendapatan Petani Padi di Desa Simaninggir Kecamatan Sipirok Kabupaten Tapanuli Selatan - Nur Patima Siregar; Rusydi Fauzan (ARZUSIN, 2026)
The effectiveness of fertilizer subsidy programs has become a concern in various studies, but research that specifically discusses the relationship between the effectiveness of fertilizer distribution based on the six-right indicators (6T) and changes in farmers’ income at the micro level remains limited. This study aims to analyze the effectiveness of the government’s fertilizer subsidy program on the income of rice farmers in Simaninggir Village, Sipirok Subdistrict, South Tapanuli Regency. This study employed a qualitative approach with a field research design, involving rice farmers receiving subsidized fertilizer who were selected through purposive sampling. Data were collected through structured interviews and documentation, and were then analyzed descriptively and qualitatively based on the six-right indicators (6T). The results showed that the effectiveness of the fertilizer subsidy program had not been fully optimal, with the right type and right place indicators falling into the very effective category, right price in the effective category, right time and right quality in the moderately effective category, and right quantity in the ineffective category. In addition, the findings revealed an average decrease in farmers’ income of 1.19%, an increase in production costs of 3.28%, and a decline in profit of 2.50% during the 2024–2025 period. These findings indicate that the accuracy of the quantity and timing of fertilizer distribution plays an important role in supporting the success of the fertilizer subsidy program and improving farmers’ welfare. The conclusion of this study affirms the need to improve the distribution system of subsidized fertilizer so that its implementation becomes more effective, while also contributing theoretically to studies of agricultural policy and farm economics and providing practical implications for the government and stakeholders in improving the effectiveness of the fertilizer subsidy program.